Cerração de choradeira - Pires, Mariana Rennhack (2016)
This dissertation consists of a fictional text (a novel called Cerração de choradeira) and a creation report. The novel aims to follow the steps of Death and her “employees” (carpideiras), whose task is to mourn the dead ones in memorial services, most frequent without even knowing them. This story’s protagonist is Astúcia, a lady from a family of migrants who mourns in an isolated location at the South of Brazil (Rio Grande do Sul). Cerração de choradeira follows her path, her partnership with Death itself, and the effect that this particular relationship has on other characters’ way to confronting the Inevitable. In order to obtain this broaden perspective, the novel tries to work with different points of view and storylines.